2013
DOI: 10.1128/aem.00011-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Tetramethylpyrazine Catabolic Pathway in Rhodococcus jostii TMP1

Abstract: bAt present, there are no published data on catabolic pathways of N-heterocyclic compounds, in which all carbon atoms carry a substituent. We identified the genetic locus and characterized key reactions in the aerobic degradation of tetramethylpyrazine in Rhodococcus jostii strain TMP1. By comparing protein expression profiles, we identified a tetramethylpyrazine-inducible protein of 40 kDa and determined its identity by tandem mass spectrometry (MS-MS) de novo sequencing. Searches against an R. jostii TMP1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…We previously showed that TpdE is able to reduce carbonyl group of N-(butan-3-one-2yl)acetamide (Kutanovas et al, 2013). In this study we demonstrated that TpdE is also capable of reducing diacetyl when NADPH was used as a co-substrate.…”
Section: Tpde Substrate Range and Biochemical Characterizationsupporting
confidence: 58%
“…We previously showed that TpdE is able to reduce carbonyl group of N-(butan-3-one-2yl)acetamide (Kutanovas et al, 2013). In this study we demonstrated that TpdE is also capable of reducing diacetyl when NADPH was used as a co-substrate.…”
Section: Tpde Substrate Range and Biochemical Characterizationsupporting
confidence: 58%
“…The opening of the epoxide to a diol was presumed to be a plausible pathway for indole-2,3-dihydrodiol formation (44). Moreover, the oxidation of several N-heterocyclic compounds catalyzed by monooxygenases when two oxygen atoms (one from oxygen, another from water) were inserted was described recently (45)(46)(47). A similar mechanism for bacterial degradation of indole acetic acid was described (48) involving the intermediate dioxindole-3-acetic acid (DOAA), a structural analogue of 3-hydroxyindolin-2-one in indole degradation.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a large amount of TpdE, the overexpression of the recombinant protein was performed as described previously ( Kutanovas et al, 2013 ) with slight modifications. E. coli BL21 (DE3) cells harbouring pET- tpdE were grown in BHI medium (supplemented with 50 mg/ml ampicillin) to an OD 600 of 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have shown that the protein TpdE from Rhodococcus jostii TMP1 is involved in the catabolism of tetramethylpyrazine, where it reduces N -(butan-3-one-2-yl)acetamide ( Fig. 1 ) ( Kutanovas et al, 2013 ). Here we provide a biochemical characterization of TpdE.…”
Section: Introductionmentioning
confidence: 99%